Business Model Canvas Produk EasyBath (3in1 Antimicrobial Waterless Bath Spray) - Fauziyah, Aulia Hasna; Ramadhani, Ingrid Putri; Perdana, Hafizh Hadian; Faza, Nadif Muhammad; Dewi, Vira Kusuma; Yudha, Eka Purna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
EasyBath is an innovative product that serves as a solution for environmentally friendly soap. In developing its product, EasyBath needs a business strategy to increase awareness and target market segments. The purpose of this research is to describe the business performance and present the business model of the EasyBath product. This research employs a case study research method on the EasyBath product business. The data analysis used is the Business Model Canvas of the EasyBath product business. The results show that EasyBath products have 7 advantages, including 3in1 functionality, natural ingredients, eco-friendly, cultural value, travel-friendly, skin moisturization, and long-lasting fragrance up to 4 hours. With raw materials from UMKM in Jatinangor, EasyBath production involves drying, maceration, distillation, soap making, mixing, quality control, and packaging. The selling price is based on the cost of production with marketing techniques, such as discounts, social media promotion, giveaways, direct selling, and campaigns. Furthermore, EasyBath products target various consumer segments, especially tourists, travelers, nature lovers, environmentalists, disaster volunteers, and field workers. EasyBath optimizes offline and online distribution channels, implements various marketing strategies, builds customer relationships with responsive service, and generates income from direct sales, distributors, and cooperation with stores. Thus, when considering total production costs including materials, rent, transportation, and others, it amounts to Rp11,019,758.00. Through effective marketing targeting, EasyBath has the potential to become a popular choice for the public.